2017
DOI: 10.5370/jeet.2017.12.1.420
|View full text |Cite
|
Sign up to set email alerts
|

WLDF: Effective Statistical Shape Feature for Cracked Tongue Recognition

Abstract: -This paper proposes a new method using Wide Line Detector based statistical shape Feature (WLDF) to identify whether or not a tongue is cracked; a cracked tongue is one of the most frequently used visible features for diagnosis in traditional Chinese Medicine (TCM). We first detected a wide line in the tongue image, and then extracted WLDF, such as the maximum length of each detected region, and the ratio between maximum length and the area of the detected region. We trained a binary support vector machine (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Wang et al [9] realized the prickles extraction on the green tongue image, with an accuracy of 88.47%. Yet, due to the complex and diverse tongue features, classical image processing methods have some problems, such as space-time consumptive algorithm, difficulties in automated high-throughput processing, and weak migration ability in correlation research [10][11][12], which make the comprehensive analysis of tongue images unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [9] realized the prickles extraction on the green tongue image, with an accuracy of 88.47%. Yet, due to the complex and diverse tongue features, classical image processing methods have some problems, such as space-time consumptive algorithm, difficulties in automated high-throughput processing, and weak migration ability in correlation research [10][11][12], which make the comprehensive analysis of tongue images unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…In general, CNN architectures can avoid feature selection manually and automatically extract features, which are key elements to enable the intelligent tongue diagnosis system into the TCM clinical practice. Although several previous studies have reported encouraging results using CNN methods to extract tongue image features for tongue color (tongue body and tongue coating) classi cation [16][17][18], tongue image characteristic recognition (tooth-marked tongue [19][20][21], cracked tongue [22,23]) and tongue image segmentation [24][25][26][27][28][29][30], but they usually ignore the quality of tongue images, which is strongly related to the accuracy of TCM diagnosis. Thus, the medical application of deep learning methods to the eld of tongue diagnosis has not achieved much so far.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [16] compared the performance of the watershed algorithm and the Weber local descriptor in fissure extraction, and discovered that the former performed better; however, Zhang focused only on identifying tagged pixels of fissures with certain thresholds without using an effective classifier. Therefore, Li et al [17] improved Zhang's method using the Otsu threshold and histogram equalization. Finally, an SVM was used to recognize fissured tongue, and the identification accuracy increased.…”
Section: U N C O R R E C T E D P R O O F V E R S I O Nmentioning
confidence: 99%
“…In general, although previous studies have realized significant achievements in the field of fissured tongue recognition, some important issues still need to be explored. Firstly, the sample size of the datasets was relatively small (e.g., less than 1000 for [15][16][17]), which may restrict the generalization of the classification models. Secondly, all methods used handcrafted features, although some minor details were difficult to describe.…”
Section: U N C O R R E C T E D P R O O F V E R S I O Nmentioning
confidence: 99%